Automated fertilizer mixer system for fertigation farming / Mohd Khairi Nordin …[et al.] - Nordin, Mohd Khairi; Mohd Yassin, Ahmad Ihsan; Md Tahir, Nooritawati; Saaid, M.F. (Universiti Teknologi MARA, 2021)
This paper describes the automatic fertilizer mixer for fertigation farming system using microcontroller. The purpose of this project is to study the effectiveness of the system in mixing the raw ingredients of fertilizers into either set A or set B fertilizers using a low-cost system. An Arduino microcontroller, LCD, keypad, and motors used to operate the system for separating the raw ingredients and mixing it to form the result of fertilizer mixtures. The final mixture results referred to as the amount of the raw ingredients recorded for a specific level of water by adhering to the given formula. After several experiments conducted, this technique proven to be an effective way of separating and mixing the fertilizers mixtures. The mixture ingredients were successfully mixed, and the given formula was strictly followed. The combination had been mixed with a low weight percentage of error by separating it using this developed system. The overall functions of the system have met the objectives by successfully combining the mixture